2003
DOI: 10.1149/1.1571532
|View full text |Cite
|
Sign up to set email alerts
|

Rechargeable Lithium Sulfur Battery

Abstract: In this paper, the structural change of the sulfur cathode during the electrochemical reaction of a lithium sulfur battery employing 0.5 M LiCF 3 SO 3 -tetra͑ethylene glycol͒ dimethyl ether ͑TEGDME͒ was studied by means of scanning electron microscopy ͑SEM͒, X-ray diffraction ͑XRD͒, and wave dispersive spectroscopy ͑WDS͒. The discharge process of the lithium sulfur cell could be divided in the first discharge region ͑2.4-2.1 V͒ where the reduction of elemental sulfur to form soluble polysulfides and further re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
270
5
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 505 publications
(303 citation statements)
references
References 8 publications
11
270
5
6
Order By: Relevance
“…Two discharge plateaus in the range of 2.4-2.1 V and 2.1-1.7 V, respectively, were observed, which are related to the stepwise reactions between Li 2 S and solid S 8 molecules [8]. The second discharge plateau was more sensitive to the discharge C rate [55], consequently, all the cathodes revealed decreased utilization of sulfur and increased overpotentials as the discharge C-rate increased. Both the #8 and #5-Li 2 S/G@C could undergo reversible redox reactions at higher C rates, however, #8-Li 2 S/G@C showed the lowest charge and discharge overpotentials at each C rate and exhibited a stable plateau even at the high C rate of 2 C, demonstrating a remarkable electronic conductivity and the lowest energy loss associated with charge/discharge overpotentials owing to the combination of the highly conductive graphene substrate and the carbon coating.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Two discharge plateaus in the range of 2.4-2.1 V and 2.1-1.7 V, respectively, were observed, which are related to the stepwise reactions between Li 2 S and solid S 8 molecules [8]. The second discharge plateau was more sensitive to the discharge C rate [55], consequently, all the cathodes revealed decreased utilization of sulfur and increased overpotentials as the discharge C-rate increased. Both the #8 and #5-Li 2 S/G@C could undergo reversible redox reactions at higher C rates, however, #8-Li 2 S/G@C showed the lowest charge and discharge overpotentials at each C rate and exhibited a stable plateau even at the high C rate of 2 C, demonstrating a remarkable electronic conductivity and the lowest energy loss associated with charge/discharge overpotentials owing to the combination of the highly conductive graphene substrate and the carbon coating.…”
Section: Resultsmentioning
confidence: 93%
“…3a, even though good capacities can be obtained with #3, #5 and #8-Li 2 S/G@C cathodes at 0.2 C, the specific capacity of the #3 and #5-Li 2 S/G@C composite cathodes dramatically decreased as the discharge rate increased. This capacity loss with increased rates is directly associated with the conductivity of the cathodes [55]. In contrast, the #8-Li 2 S/G@C cathode showed the best rate capability and delivered specific capacities of 1029.8 mA h g À 1 of Li 2 S (1472 mA h g À 1 of S), 831.6 mA h g À 1 of Li 2 S (1189 mA/ h g À 1 of S), 769 mA h g À 1 of Li 2 S (1099 mA h g À 1 of S) and 672.8 mA h g À 1 of Li 2 S (962 mA h g À 1 of S) at charge/discharge rates of 0.2 C, 0.5 C, 1.0 C and 2.0 C (1.0 C ¼1166 mA h g À 1 Li 2 S), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The structural changes of sulfur cathode during the charge-discharge process of a Li/S cell employing a liquid electrolyte (0.5 M LiCF 3 SO 3 in TEGDME) have been investigated in detail by Cheon et al using SEM, XRD and wave dispersive spectroscopy (WDS) [14]. The cathode morphology examination at different depths of discharge has shown a significant change in morphology at the end of the lower (2.1 V) plateau.…”
Section: Electrochemical Characteristics Of Li/s Batteriesmentioning
confidence: 99%
“…The influence of sulfur cathode thickness (varied as 15, 30 and 60 µm) on the discharge capacity of Li/ S cell was investigated by Cheon et al [14]. It was observed that an increase in thickness resulted in a decrease in sulfur utilization at all current rates, as a result of the thicker insulative layer of sulfur.…”
Section: Cathode Preparationmentioning
confidence: 99%
“…The rechargeable lithium-sulfur (Li-S) battery has attracted immense assiduity in the last several years [4][5][6] owing to its high energy density (theoretically 2567 Wh/kg) and high theoretical specific capacity (1675 mAh/g). It exhibits higher specific capacity and specific energy (with lithium anode) than any other known cathode active materials [7,8] . In addition to, sulfur is abundant in nature, inexpensive and environmental harmless.…”
Section: Introductionmentioning
confidence: 95%